American Burn Association Guidelines on the Management of Acute Pain in the Adult Burn Patient: A Review of the Literature, a Compilation of Expert Opinion, and Next Steps. Issue 6 (30th November 2020) - Romanowski, Kathleen S; Carson, Joshua; Pape, Kate; Bernal, Eileen; Sharar, Sam; Wiechman, Shelley; Carter, Damien; Liu, Yuk Ming; Nitzschke, Stephanie; Bhalla, Paul; Litt, Jeffrey; Przkora, Rene; et al.
Abstract: The ABA pain guidelines were developed 14 years ago and have not been revised despite evolution in the practice of burn care. A sub-committee of the American Burn Association's Committee on the Organization and Delivery of Burn Care was created to revise the adult pain guidelines. A MEDLINE search of English-language publications from 1968 to 2018 was conducted using the keywords "burn pain, " "treatment, " and "assessment." Selected references were also used from the greater pain literature. Studies were graded by two members of the committee using Oxford Centre for Evidence-based Medicine—Levels of Evidence. We then met as a group to determine expert consensus on a variety of topics related to treating pain in burn patients. Finally, we assessed gaps in the current knowledge and determined research questions that would aid in providing better recommendations for optimal pain management of the burn patient. The literature search produced 189 papers, 95 were found to be relevant to the assessment and treatment of burn pain. From the greater pain literature 151 references were included, totaling 246 papers being analyzed. Following this literature review, a meeting to establish expert consensus was held and 20 guidelines established in the areas of pain assessment, opioid medications, nonopioid medications, regional anesthesia, and nonpharmacologic treatments. There is increasing research on pain management modalities, but available studies are inadequate to create a true standard of care. We call for more burn specific research into modalities for burn pain control as well as research on multimodal pain control.